Pediatric stroke: cerebrovascular injury in the developing brain - Kirton, Adam (Henry Stewart Talks, 2020)
Stroke in neonates and children, Arterial ischemic stroke, Cerebral sinovenous thrombosis, Hemorrhagic stroke, Acute diagnosis and management of childhood stroke, Etiology and investigation of childhood stroke, Treatment and prevention in childhood stroke, Diagnosis and types of perinatal stroke, Pathogenesis of perinatal stroke, Outcomes from perinatal and childhood stroke, Imaging applications for diagnosis and developmental plasticity, Rehabilitation strategies, Patient and family centered outcomes & supportive management